A Functional MicroRNA Screening Method for Organ Morphogenesis. Issue 1 (3rd March 2017) - Rebustini, Ivan T.
Abstract: The increasing repertoire of microRNAs expressed during organ development and their role in regulating organ morphogenesis provide a compelling need to develop methods to assess microRNA function using various in vitro and in vivo experimental models. Methods to assess microRNA function during organ morphogenesis include transfection of microRNA inhibitors (antagomirs) and activators (mimics) into mouse embryonic explanted organs using liposomes, which can potentially result in low efficiency of transfection and off‐target effects. We devised a method to assess microRNA function in explanted organs by transfecting antagomirs and mimics using peptide‐based nanoparticles, increasing functional microRNA targeting efficiency, and decreasing off‐target effects. Our method can be applied to a variety of embryonic organs that can be explanted and provides an alternative to efficiently and functionally prioritize microRNAs during organ morphogenesis for further in vivo genetic approaches. © 2017 by John Wiley & Sons, Inc.